2003
DOI: 10.1128/jvi.77.3.2071-2080.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reverse Transcriptase Variants, Drugs, and Vpr on Human Immunodeficiency Virus Type 1 Mutant Frequencies

Abstract: The evolution of drug resistance is a major complication of human immunodeficiency virus type 1 (HIV-1) chemotherapy. HIV-1 reverse transcriptase (RT) is a major target of antiretroviral therapy and ultimately the target of drug resistance mutations. Previous studies have indicated that drug-resistant HIV-1 RTs can alter HIV-1 mutant frequencies. In this study, we have tested a panel of HIV-1 RT variants for their ability to influence virus mutant frequencies. The RT variants tested included drug-resistant RT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 65 publications
(66 reference statements)
7
70
0
Order By: Relevance
“…We demonstrate that the Vpr-dependent incorporation of UNG into HIV-1 particles is directly responsible for the role of Vpr in the in vivo modulation of the virus mutation rate (11,12). Moreover, our results show that the incorporation of UNG into virions is critical for efficient replication of HIV-1 in primary non-dividing cells such as macrophages.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…We demonstrate that the Vpr-dependent incorporation of UNG into HIV-1 particles is directly responsible for the role of Vpr in the in vivo modulation of the virus mutation rate (11,12). Moreover, our results show that the incorporation of UNG into virions is critical for efficient replication of HIV-1 in primary non-dividing cells such as macrophages.…”
Section: Discussionmentioning
confidence: 58%
“…Although the viral integrase may also participate in this recruitment (22,23), the Vpr-dependent packaging of UNG2 into virions strikingly correlated with the ability of Vpr to influence the mutation rate of HIV-1 (24). This indicated that the interaction between Vpr and UNG2 may directly influence the reverse transcription accuracy and, thus, play a role in the modulation of the in vivo mutation rate of HIV-1 (11,12).…”
mentioning
confidence: 93%
See 3 more Smart Citations